Associations Between Smoking Abstinence, Inhibitory Control, and Smoking Behavior: An fMRI Study - Bell, Spencer; Froeliger, Brett (Frontiers in Psychiatry, 2021)
Nicotine addiction is associated with dysregulated inhibitory control (IC), mediated by corticothalamic circuitry including the right inferior frontal gyrus (rIFG). Among sated smokers, worse IC task performance and greater IC-related rIFG activity have been shown to be associated with greater relapse vulnerability. The present study investigated the effects of smoking abstinence on associations between IC task performance, rIFG activation, and smoking behavior. Smokers (N = 26, 15 female) completed an IC task (Go-Go/No-go) during fMRI scanning and a laboratory-based smoking relapse analog task (SRT) on two visits: once when sated and once following 24 hours of smoking abstinence. During the SRT, smokers were provided with monetary rewards for incrementally delaying smoking. The interaction between smoking state (abstinent vs. sated) and No-go trial accuracy on latency to smoke during the SRT was non-significant, indicating a similar relationship between IC and SRT task performance across states. Moreover, the interaction between smoking state and IC-related rIFG activation on SRT performance was non-significant. Main effects of smoking state in both of these models were also non-significant while main effects of No-go accuracy and rIFG IC-Activation were both significant when collapsing across states: higher No-go accuracy was associated with smoking later and higher rIFG IC-Activation was associated with smoking sooner. Post-hoc whole brain analyses indicated that abstinence resulted in greater IC-related activity in the right middle frontal gyrus (MFG) and insula. Activation during IC in these regions was significantly associated with decreased No-go accuracy. Moreover, greater abstinence induced activity in right MFG during IC was associated with smoking sooner on the SRT. These findings bolster the extant literature on the effects of nicotine on executive function but also contribute novel insights on how individual differences in behavioral and neuroimaging measures of IC may influence relapse propensity independent of smoking state.